Synthesis and characterization of ultra violet curable renewable polymer graphite composites - Abdullah, Nur Munirah (2019)
This thesis aims is to evaluate the synthesis and characterization of ultra violet (UV) curable renewable polymer graphite (RPG) composites. Accordingly, the renewable polymeric composites were prepared through a film slip casting method at room temperature wherein graphite particles of various weight loadings were mixed with mass proportion 2:1 of renewable monomer and Methylene Diphenyl Diisocyanate, MDI respectively. The main concerned was given to renewable monomer based vegetable cooking oil produced at the SPEN-AMMC UTHM. The morphology-structural relation of the RPG composites confirmed that the graphite particles contain functional groups such as hydroxyl and carboxylic groups are randomly distributed and attributed to formation of interconnected interface within the polymeric composites. Furthermore, as the graphite particle loading increased, the thermal degradation temperature at three distinct decomposition stages shifted and to some extent, resulting in much higher crystallinity. As expected, the mechanical properties of the composites were also enhanced with the modulus and tensile strength increment up to ~440% and ~100% respectively. Significantly, all of these results correlate with viscoelastic properties in which the composites achieved percolation threshold at RPG20 composites. Moreover, the decreased in optical energy band gap (Eg) which afterwards took the leads to electrical conductivity (σ). Aptly, the composites (RPG20, RPG25 and RPG30) were found to possess favorable electrical conductivity range of 10-5 – 10-4 S/m, while all other samples were deemed to be not conductive due to improper dispersion of graphite particulates. On the contrary, UV curable composites did not show any significant enhancement and graphite particle acted as UV stabilizer in this manner. Therefore, the stability of the conductive renewable polymer graphite composite is suitable to be used in various composites applications.